Multigram scale synthesis of 3, 4- and 3, 6-dihydro-2H-thiopyran 1, 1-dioxides and features of their NMR spectral behavior. Issue 17 (2nd September 2018) - Chabanenko, Roman M.; Yu. Mykolenko, Svitlana; Kozirev, Eugene K.; Palchykov, Vitalii A.
Abstract: A new four-step synthesis of 3, 4- and 3, 6-dihydro-2 H -thiopran-1, 1-dioxides from dihydro-2 H -thiopyran-3(4 H )-one is reported. The title compounds are synthesized starting with oxidation of the ketone with a 30% aqueous solution of hydrogen peroxide in a mixture of AcOH-Ac2 O. The keto group is then reduced by sodium borohydride followed by mesylation and elimination of methanesulfonic acid under basic conditions (pyridine for 3, 4-isomer and aqueous NaOH for 3, 6-isomer). This sequence is simpler, than previously known methods, uses cheaper and more readily available reagents, and leads to 2 H -thiopran-1, 1-dioxides on multigram scale with 64% and 74% total yields, respectively. The structure and purity of the compounds were confirmed by 2D NMR and GCMS methods. The proposed method expands the means to access functionalized cyclic sulfones as building blocks in the synthesis of combinatorial libraries of new biologically active compounds. Graphical Abstract: